NEW RECORDS FOR NEMATODES OF TURTLES (REPTILIA:TESTUDINES) FROM PERU - Salizar, Patricia (2007)
Klossinemella conciliatus Alho, 1964 and Paraorientatractis semiannulata Gibbons, Khalil & Marinkelle, 1997 we have found for the first time to Yellow-spotted Amazon River turtle Podocnemis unifilis Troschel, 1848 from Peru. Also, Atractis impura Caballero, 1944 and Angusticaecum brevispiculum Chapin, 1925 are recorded for Yellow-footed tortoise, Geochelone denticulate (Linnaeus, 1766).